A Development Methodology for Copper End Termination Paste — Part 1: Origin of Green Defects. (2002) - Kumar, Umesh
Abstract : Copper (Cu) based pastes have emerged as the termination materials of choice for ceramic capacitors with base metal internal electrodes. To prevent oxidation of nickel (Ni) internal electrode and the copper terminations, it is necessary to fire the terminations in a nitrogen atmosphere. This requirement places significant restrictions on raw material selection for the termination pastes. For example, acrylic-based resins are used as organic binder for their clean burning characteristics over the traditional ethyl cellulose based binder system. As the viscoelastic behavior of acrylic resin systems are different to those of cellulose systems, differences are observed in the flow behavior of the paste. In this paper, the influence of paste rheology on the green cosmetic defects such as mooning, peaking, etc. is discussed. Additionally, the influence of process condition such as dipping parameters, drying conditions etc., on the green cosmetic defects are discussed. Finally, properties of a copper termination, which can be processed between 800–825°C, are discussed.